Overview of Routine Blood Test Results in Rheumatoid Arthritis Patients in Ciamis Regency - Rahayu Nirmatul Mutmainah; Muhammad Abdul Hadi Rabbani; Rizal Hanif (LPPM STIKes Muhammadiyah Ciamis, 2025)
Background & Objectives: Based on data from the Ciamis District Health Service Profile (2022), rheumatoid arthritis (RA) ranks 6th out of the 10 most common diseases at community health centers, with 16,195 cases. Systemic inflammation in RA can affect blood cell productivity. This has the potential to cause blood abnormalities, which can lead to diseases such as anemia, leukemia, or blood clotting problems. Routine blood tests are performed as a screening test to determine blood values in RA patients. The purpose of this study was to determine the results of routine blood tests in RA patients in Ciamis Regency. Method: This study used a descriptive method with total sampling technique. The examination was conducted on RA patients in Ciamis Regency in May 2024 with a sample size of 20 respondents. The study used secondary data that was processed into diagrams and then explained narratively. The study used a hematology analyzer located in the hematology laboratory of Ciamis Regional General Hospital. Results: This study found that the percentage of normal blood values for erythrocyte parameters was 70%, hemoglobin was 70%, hematocrit was 70%, average erythrocyte index was normal at 90%, leukocytes were 95%, average leukocyte types were normal at 80%, and thrombocytes were 90%. Low values were found in the erythrocyte (30%), hemoglobin (30%), hematocrit (30%), MCV (25%), MCH (10%), RDW SD (10%), and lymphocyte (11%) parameters. Meanwhile, high values were found in the parameters of white blood cells (10%), lymphocytes (8%), monocytes (15%), neutrophils (10%), eosinophils (40%), basophils (5%), and platelets (10%). Conclusion: It can be concluded that the values for erythrocytes, hemoglobin, hematocrit, erythrocyte indices, leukocytes, leukocyte types, and platelets were generally within the normal range.